Social causes of teenage pregnancy : the case of an informal settlement, Polokwane, South Africa - Mphahlele, Rasekele Bridgette (My University, 2024)
The purpose of this study was to explore the social causes of teenage pregnancy in an informal settlement in Polokwane, South Africa. The study also examined factors that contribute to, and have an impact on, teenage pregnancy. An exploratory qualitative research method was employed to explore social causes of teenage pregnancy in an informal settlement at Polokwane, South Africa. The research participants of the study were purposively sampled 16 teenage mothers between the ages of 15-19 and residing in Extension 78, Polokwane. Data collection was done using semi-structured interviews. The collected data was analysed using a thematic analysis approach. The findings of the study reveal that teenage pregnancy can be attributed to multiple factors that include the failure of existing policies to mitigate or limit the prevalence of teenage pregnancy, transactional relationships between teenagers and elderly men, and a lack of accessible adequate healthcare services. This study recommends a holistic approach by the state departments concerned with teenage pregnancy, local communities, NGOs and scholars, who should collaborate in implementing suggested interventions to mitigate teenage pregnancy and its effects. To ensure effective implementation of legislative frameworks, it is essential to enhance progressive interventions and accountability measures in areas where they may be lacking and areas that have high numbers of teenage pregnancies.
Thesis (M. A. (Sociology)) -- University of Limpopo, 2024
Keywords: Teenage pregnancy; Social causes of teenage pregnancy; Extension 78; Polokwane; Limpopo Province; Teenage pregnancy -- South Africa; Pregnancy -- Psychological aspects; Squatter settlements